Multiple Ligands Targeting Cholinesterases and β‐Amyloid: Synthesis, Biological Evaluation of Heterodimeric Compounds with Benzylamine Pharmacophore. Issue 8 (29th May 2015) - Szałaj, Natalia; Bajda, Marek; Dudek, Katarzyna; Brus, Boris; Gobec, Stanislav; Malawska, Barbara
<x xml:space="preserve">Abstract</x> Alzheimer's disease (AD) is a fatal and complex neurodegenerative disorder for which effective treatment remains the unmet challenge. Using donepezil as a starting point, we aimed to develop novel potential anti‐AD agents with a multidirectional biological profile. We designed the target compounds as dual binding site acetylcholinesterase inhibitors, where the N‐benzylamine pharmacophore is responsible for interactions with the catalytic anionic site of the enzyme. The heteroaromatic fragment responsible for interactions with the peripheral anionic site was modified and three different heterocycles were introduced: isoindoline, isoindolin‐1‐one, and saccharine. Based on the results of the pharmacological evaluation, we identified compound 8b with a saccharine moiety as the most potent and selective human acetylcholinesterase inhibitor (IC50 = 33 nM) and beta amyloid aggregation inhibitor. It acts as a non‐competitive acetylcholinesterase inhibitor and is able to cross the blood–brain barrier in vitro. We believe that compound 8b represents an important lead compound for further development as potential anti‐AD agent.